The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1097/brs.0b013e318296232f
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Controlled Clinical Investigation Comparing PCM Cervical Disc Arthroplasty With Anterior Cervical Discectomy and Fusion

Abstract: The treatment of symptomatic single-level cervical spondylosis with PCM achieves clinical outcomes that are at least equivalent to ACDF while maintaining motion. At 2 years, patients with PCM had lower NDI scores, statistically lower rate of prolonged dysphagia, greater patient satisfaction, and superior overall success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
99
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(106 citation statements)
references
References 47 publications
3
99
4
Order By: Relevance
“…Fusion rates of ACDF with cervical plating have been estimated to be 97.1% for single-level procedures 33. Comparatively, randomized control clinical trials involving patients treated with ACDF with anterior plating and allograft bone had fusion rates of 89% to 96.6% at 24 months 3438…”
Section: Discussionmentioning
confidence: 99%
“…Fusion rates of ACDF with cervical plating have been estimated to be 97.1% for single-level procedures 33. Comparatively, randomized control clinical trials involving patients treated with ACDF with anterior plating and allograft bone had fusion rates of 89% to 96.6% at 24 months 3438…”
Section: Discussionmentioning
confidence: 99%
“…Several Level I evidence randomized clinical trials have confirmed both the safety and efficacy of TDR in both the short-and long-term. [8][9][10][11][12][13][14] TDR has shown to have many possible advantages over ACDF including lower rates of subsequent surgical intervention, 15,16 lower rates of adjacent segment degeneration, 13,17,18 and an advantage in cost-effectiveness. 19,20 Furthermore, kinematic analyses have shown TDR to maintain functional biomechanics at the level treated while mitigating excess motion at adjacent segments.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the prior IDE studies, Phillips et al reported similar reoperation rates (ACDF 5.4%, ACDA 5.2%) at two-year follow-up with a different implant design. [22]…”
Section: Discussionmentioning
confidence: 99%